Microbial iron transport via a siderophore shuttle: A membrane ion transport paradigm - Stintzi, Alain (The National Academy of Sciences, 2000)
A mechanism of ion transport across membranes is reported. Microbial transport of Fe(3+) generally delivers iron, a growth-limiting nutrient, to cells via highly specific siderophore-mediated transport systems. In contrast, iron transport in the fresh water bacterium Aeromonas hydrophila is found to occur by means of an indiscriminant siderophore transport system composed of a single multifunctional receptor. It is shown that (i) the siderophore and Fe(3+) enter the bacterium together, (ii) a ligand exchange step occurs in the course of the transport, and (iii) a redox process is not involved in iron exchange. To the best of our knowledge, there have been no other reports of a ligand exchange mechanism in bacterial iron transport. The ligand exchange step occurs at the cell surface and involves the exchange of iron from a ferric siderophore to an iron-free siderophore already bound to the receptor. This ligand exchange mechanism is also found in Escherichia coli and seems likely to be widely distributed among microorganisms.